APPLICATION OF APM WINMACHINE SOFTWARE FOR DESIGN AND CALCULATIONS IN MECHANICAL ENGINEERING - Neduzha, L. O.; Shvets, A. O. (Science and Transport Progress, 2016)
Purpose.To conduct the research at all stages of design, development, operation, residual operation life determination, namely, preliminary study, action principle choice, design of draft and technical projects, their optimization, preparation of design documentation and control information for automated production, comprehensive engineering analysis, it is required to use the latest computer technologies. Their use can not only present data and information in some way, but also gives the opportunity to effectively and directly interact with the information object that is created or demonstrated. Methodology.To perform engineering calculations associated with the analysis of the strength of machines, mechanisms, constructions one uses both analytical and numerical methods in practice.The most common method for analysing the stress-strain state of object models, obtaining their dynamic and stability characteristics at constant and variable modes of external load is the finite element method, which is implemented in many famous and widespread software products, providing strength calculation of models of machines, mechanisms and structures. Findings.The use of modern software for designing machine parts and various types of their joints and for strength analysis of structures is justified. Colour charts for distribution of stresses, displacement, internal efforts, safety factor and others allow accurate and quick identification of the most dangerous places in the structure. The program also provides an opportunity to «look» inside the elements and see the resulting distribution of internal force factors. Originality.The paper considered the aspects, which are unexplored at present, associated with the current state and prospects of development of industrial production, the use of software package for design and calculations in the mechanical industry. The result of the work is the justification of software application for solving problems that are aimed at using research findings for various practical tasks in specific fields of mechanical engineering. Practical value.Compared with other software systems, popularity of the considered one is explained by easy mastering of the system, quick implementation both in training and in production process The organizational structure, «friendly» graphical interface and accessible language make learning and use of the program very convenient. These and other factors actually reduce the time for project implementation, emphasize the relevance and the practical importance of the software system, which is appreciated by its users.